2016
DOI: 10.7717/peerj.1549
|View full text |Cite
|
Sign up to set email alerts
|

In plantacomparative transcriptomics of host-adapted strains ofRalstonia solanacearum

Abstract: Background. Ralstonia solanacearum is an economically important plant pathogen with an unusually large host range. The Moko (banana) and NPB (not pathogenic to banana) strain groups are closely related but are adapted to distinct hosts. Previous comparative genomics studies uncovered very few differences that could account for the host range difference between these pathotypes. To better understand the basis of this host specificity, we used RNAseq to profile the transcriptomes of an R. solanacearum Moko strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 31 publications
2
37
0
1
Order By: Relevance
“…Analysis of xylem sap from different plant species showed potassium as the most abundant mineral nutrient, followed by nitrate and chloride (Fatima and Senthil‐Kumar, ). Global expression analyses have been used to understand how R. solanacearum survives and succeeds within the host xylem (Brown and Allen, ; Jacobs et al ., ; Ailloud et al ., ). In an initial study using in vivo expression technology, 153 unique genes were shown to be induced in planta (Brown and Allen, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Analysis of xylem sap from different plant species showed potassium as the most abundant mineral nutrient, followed by nitrate and chloride (Fatima and Senthil‐Kumar, ). Global expression analyses have been used to understand how R. solanacearum survives and succeeds within the host xylem (Brown and Allen, ; Jacobs et al ., ; Ailloud et al ., ). In an initial study using in vivo expression technology, 153 unique genes were shown to be induced in planta (Brown and Allen, ).…”
Section: Introductionmentioning
confidence: 97%
“…R. solanacearum phylotypes partly explain the broad host range of this species complex and differential gene expression associated with host range variation has been reported recently (Ailloud et al ., ). Two closely related strains belonging to distinct R. solanacearum pathotypes were compared; a Moko strain (pathogenic to banana but not to cucurbits) and a NPB strain (pathogenic to cucurbits but not to banana).…”
Section: Introductionmentioning
confidence: 97%
“…R. solanacearum has an unusually wide host range, infecting more than 200 species belonging to more than 54 botanical families, including economically-important crops [ 2 , 3 , 4 ]. It represents a heterogeneous group subdivided into five races based on host range, five biovars based on physiological and biochemical characteristics [ 5 , 6 ], and four phylotypes roughly corresponding to geographic origin [ 7 , 8 ]. It can survive in soil for many years and can spread through water, rhizosphere contact, and farming [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ailloud et al . () performed transcriptome analyses of R. solanacearum strains infecting host plants using RNA‐seq, and many virulence‐related genes were differentially expressed during infection, compared with in vitro growth, such as growth on a rich medium. A large majority of the PhcA controlled genes followed the same regulation pattern in both rich medium in vitro and after in planta growth, except for a set of HrpG‐HrpB regulated genes, including the type III secretion machinery and type III effectors, whose genes appeared to be specifically induced by PhcA in the plant environment, whereas this regulator repressed their expression in rich medium (Perrier et al ., ).…”
Section: Discussionmentioning
confidence: 99%